Cobalt atom collapsed in a single chain of polymethyl methacrylate and its zinc oxide nanocomposite, thermal, electrical, and optical behaviors - Zebari, Osama Ismail Haji; Demirelli, Kadir; Zeebaree, Samie Yaseen Sharaf; Tuncer, Hulya (Sage Publications Ltd, 2024)
The copolymer precursor, poly [4-(4-vinylbenzyl)oxy)phthalonitrile]-co-methyl methacrylate (poly (VBOPN-co-MMA)), was synthesized through copolymerization of VBOPN and MMA at a temperature of 110 degrees C. Subsequently, a single-chain polymer complex of cobalt phthalocyanine (SCP-CoPc) was formed at 150 degrees C by intramolecular macrocyclization between the cobalt and the phthalonitrile group in poly (VBOPN-co-MMA), using excess cyclohexanol. The formation of the SCP-CoPc complex was confirmed through various spectroscopic techniques such as UV/Vis, FT-IR, 1H-NMR, and 13C-NMR. In particular, the disappearance of -CN band at 2232 cm-1 from FT-IR indicated the formation of the SCP-CoPc complex, while the presence of specific absorption bands in the UV/Vis spectrum further confirmed its creation. The electrical, dielectric, optical, and thermal properties of the SCP-CoPc complex and SCP-CoPc/ZnO 5% composites were investigated. The SCP-CoPc/ZnO 5 wt% nanocomposite exhibited improved dielectric and DC conductivity with increasing temperature. The activation energy (Ea) was found to be 0.35 eV for SCP-CoPc and 0.25 eV for SCP-CoPc/ZnO 5 wt% nanocomposite, indicating that the electrical conductivity followed the Arrhenius equation. The optical properties, including band gap, dielectric constant, and refractive index, were calculated for the SCP-CoPc/ZnO 5 wt% nanocomposite. The SCP-CoPc complex possessed a band gap of 2.89 eV, while the SCP-CoPc/ZnO 5 wt% nanocomposite had a slightly reduced band gap of 2.36 eV. The refractive indices of SCP-CoPc and SCP-CoPc/ZnO 5 wt% were also determined.
Keywords: Cobalt complexes single-chain polymer; atom transfer radical polymerization; thermal properties; electrical properties; optical properties